Editor Sebagai Sutradara, Analisis Semiotika Pada "Buku Tanah Air Kita" - Bayyinah Nurrul Haq (JURNAL RUPA, 2016)
Editor in the publishing world has function to keep the consistency of story line and point of view. â€œTanah Air Kitaâ€ is a book published by N.V. W. van Hoeve-Bandung that contain the work of local and foreign photographers since Dutch colonial rule until Indonesiaâ€™s independence. The research aims to discuss how the role of editor in producing a book that fits his vision about how Indonesia is supposed to be in a photo and how observers interpret.Using semiotic analysis based on the model spectator â€“ operatorâ€“spectrum. Analysis is done by categorizing photo illustration in 4 parts, which are :nature beauty,technology-natural resources, how people work, political change, then cross-checked upon their stadium- punctum. Selected photos shows the vision of N.A. Douwes Dekker about his expectation towards Indonesia, as the new nation that wants to be reckoned in the world, according to the presences.